2023
DOI: 10.1088/1361-6463/ad039b
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-induced reversible surface modification and its impact on oxygen heterogeneous recombination

José Afonso,
Luca Vialetto,
Vasco Guerra
et al.

Abstract: A novel model is developed for atomic oxygen surface kinetics in silica-like walls, introducing a plasma-induced surface modification, which may impact intermediate pressure plasma reactors. The model is the first to reproduce experimental measurements in an oxygen glow discharge operating in the pressure range between 0.27 mbar (0.2 Torr) and 4 mbar (3 Torr), showing a decrease with pressure of the O recombination probability on Pyrex between 0.27 mbar and 1 mbar. The numerical simulations suggest that a modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…As explained in the works by Guerra andMarinov 2016, Marinov et al 2017), KMC allows to obtain more accurate results than the deterministic method that takes approximations concerning the diffusion of physisorbed species. In this work, KMC is not employed, since the studied conditions are similar to those in the works by Marinov et al (2017) and by Afonso et al (2024), where it was confirmed that the KMC and deterministic results are close, within a 20% difference.…”
Section: Surface Kinetics Modelsupporting
confidence: 63%
See 4 more Smart Citations
“…As explained in the works by Guerra andMarinov 2016, Marinov et al 2017), KMC allows to obtain more accurate results than the deterministic method that takes approximations concerning the diffusion of physisorbed species. In this work, KMC is not employed, since the studied conditions are similar to those in the works by Marinov et al (2017) and by Afonso et al (2024), where it was confirmed that the KMC and deterministic results are close, within a 20% difference.…”
Section: Surface Kinetics Modelsupporting
confidence: 63%
“…This effect was attributed by Booth et al (2019) to incident ions and fast neutrals with sufficient kinetic energy to clean or chemically modify the surface, generating new adsorption sites. This idea was further developed by Afonso et al (2024). At pressures above 0.75 Torr, Booth et al (2019) found an approximate Arrhenius behaviour of γ O with the incident atom temperature.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations